Towards open building system in housing: A compilation of ibs precast panel - Abdul Rahim, Asiah; Abdul Hamid, Zuhairi; Zen, Ismawi; Ismail, Zulkefle; Mohd Kamar, Kamarul Anuar (IIUM Press, 2017)
Precast concrete has been used as cladding on buildings since the 1920s and has become increasingly popular since the 1950s. Recently the range of products has broadened as manufacturers have incorporated new design aesthetics of the variety of shapes and finishes. Panels are fabricated under controlled factory conditions to exacting tolerances and manufacturers are now producing thinner panels with simplified connections. Year round construction is possible with panels that are quickly erected at the site, providing the opportunity to rapidly enclose a building and speed up construction. The use of architectural precast wall panels can be cost effective because of reduced site construction time and site labor. The advent of larger capacity hauling and lifting equipment required for handling and erecting precast concrete elements has allowed builders to install larger panels and reduce construction time, enclosing the building more quickly. This can be very beneficial since the building industry in Malaysia is growing towards industrialization in construction by implementing Industrialized Building System (IBS).